TWO-STEP DEGLACIATION OF THE SOUTHEASTERN BARENTS SEA - Polyak L.; Lehman S.J.; Gataullin V.; Jull A.J.T. (My University, 1995)
Marine geologic evidence from the western Barents Sea shelf leaves little doubt that the area was covered by grounded ice during the last glaciation, but the pattern and timing of the subsequent deglaciation were not well determined. Here we reconstruct the timing and mechanism of ice-sheet retreat as constrained by seismic stratigraphy and lithostratigraphy and accelerator-mass-spectrometer 14C dating of foraminifera and mollusc shells in sediment borings from the southeastern Barents Sea, ;1000 km from the western shelf edge and former ice-sheet margin. The deposition of ice-proximal glaciomarine sediments upon till began at or shortly before 12.7 ka, indicating that the ice-sheet retreat—which most likely commenced along the western margin of the Barents Sea shelf at 15–14.5 ka—reached the southeastern part of the shelf in #2 ka. The subsequent accumulation of glaciomarine sediments took place in two distinct pulses (;12.7–12.1 ka and ;10.5–9.4 ka) separated by an interval of nondeposition lasting $1.5 ka. The two pulses of sedimentation were coeval with periods of increasing surface-water and air temperatures in the northern Atlantic region and accelerated eustatic sea-level rise, suggesting that the remaining retreat of the Barents Shelf ice sheet was paced by these factors.